Ergonomia e home offices: uma intervenção ergonômica no trabalho de mulheres autônomas em estado gestacional; um estudo de caso em São Luís-MA - VELOSO, Ludmilla Bragança (2023)
This era is defined by information technologies and globalization. The Home Office emerges and establishes itself as one of the main ways of organizing remote work. In the last years, especially from 2020 onwards, this production model has become essential, since human interactions have to be minimized due to the COVID-19 pandemic. The workstation at Home Office brought several challenges to the people who became its users, but mainly to pregnant women, who need to deal with her workload and all the changes imposed by her bodies and the workload, in addition to organizing the demands of the house and separating leisure and family environments at the same time. Pregnancy is understood as a natural physiological process, consisting of several adaptations and adjustments in all systems of the woman’s body, affects her in the development of her work activities, especially at Home Office. Therefore, there may be adverse results from these work actions during pregnancy. In this way, given the recent increase in the implementation of this form of work with pregnant women, this research analysed the jobs of users (self-employed workers), in intellectual professions, in the city São Luís – Ma, which aimed to promoting their quality of life, through ergonomic intervention in these areas, based on ergodesign parameters and considering the psychophysiological characteristics of the gestational state. For the development of the study, the Ergonomic Appreciation (first methodological stage of the Ergonomizing Intervention) was applied, through which it was possible to detect problems associated with these jobs and propused improvement solutions, prioritizing the health of the pregnant woman and consequentlythe baby, as well as promoting productivity and efficiency at work. In this way, problems were identified: interfacial, actional, spatial/ interior architectural, physical-environmental, accident, operational and organizational. The application of the questionnarie and the workstation assessment checklist were essential for correlating the body areas of pregnant women, which suffer greater discomfort/ pain, with the postures they assume and the furniture they use. Therefore, through the results obtained, it is concluded that working at Home Office exposes pregnant workers to various ergonomic constraints, requiring planning and significant changes in these workstations. In view of this, the study originated a conceptual proposal, which illustrates the ergonomic recommendations for Home Office used by pregnant workers.